An agricultural investment problem subject to probabilistic constraints - El Karfi, Kawtar; Henrion, René; Mentagui, Driss (Computational management science, 2022)
Motivated by a model introduced by Moiseev, we consider a problem of optimal investment into agricultural infrastructure (irrigation, storage) under uncertainty (demand, yield coefficients of soil). Unlike the risk-neutral approach of Moiseev, we formulate a risk-averse model based on joint probabilistic or chance constraints. We assume the random vector to obey a continuous Gaussian distribution. The probabilities of satisfying the demand of cereals and of not wasting excess harvest up to some given thresholds are calculated in dependence on the investment decisions in a multiperiod setting. Numerical results are presented for a small-dimensional example.